2005
DOI: 10.1590/s1678-77572005000300015
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the efficacy of low-level laser therapy (LLLT) and the microelectric neurostimulation (MENS) in the treatment of myogenic temporomandibular disorders: a randomized clinical trial

Abstract: RESUMOwww.fob.usp.br/revista or www.scielo.br/jaos bjective: The aim of the present study was to evaluate the efficacy of low-level laser therapy (LLLT) and the microelectric neurostimulation (MENS) in the treatment of patients with temporomandibular disorders (TMD). Material and methods: A sample of 19 individuals presenting with signs and symptoms of myogenic TMD was randomly divided into two groups (I -LLLT and II -MENS). Therapy was done in 10 sessions, three times a week, for one month. Patients were eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0
12

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 18 publications
0
35
0
12
Order By: Relevance
“…results it seemed to play positive effects on muscle tissue as important injuries were not observed at group III. Furthermore, although the findings of the present study were restricted to a specific set of parameters and that optimal treatment parameters (e.g., wavelength, dosage, number of treatment sessions) have not been, so far, agreed upon (Emshorff et al; Venancio et al), previous studies have been beneficial results using Infrared wavelengths (Çetiner et al;Fikáková et al;Kato et al, 2006;Kogawa et al, 2005;Leal Júnior et al, 2008).…”
Section: Resultsmentioning
confidence: 65%
“…results it seemed to play positive effects on muscle tissue as important injuries were not observed at group III. Furthermore, although the findings of the present study were restricted to a specific set of parameters and that optimal treatment parameters (e.g., wavelength, dosage, number of treatment sessions) have not been, so far, agreed upon (Emshorff et al; Venancio et al), previous studies have been beneficial results using Infrared wavelengths (Çetiner et al;Fikáková et al;Kato et al, 2006;Kogawa et al, 2005;Leal Júnior et al, 2008).…”
Section: Resultsmentioning
confidence: 65%
“…But in our study, we found a significant improvement in neck muscle pain along with TMJ muscles. Santos et al, 16 Kogawa et al, 17 Kato et al, 18 Emshoff et al, 19 Venancio Rde et al 20 observed significant pain reduction using LASER therapy. The present study gives some evidence that by treating TMJ muscle we can eliminate cervical pain as well.…”
Section: Discussionmentioning
confidence: 99%
“…Kogawa et al 17 destacam a importância do fisioterapeuta na abordagem terapêutica multidisciplinar da DTM, contribuindo para o alívio da dor musculoesquelética, reduzindo a inflamação e restaurando a função motora normal.…”
Section: Discussionunclassified